Identitas Visual pada Signage System di Borma Setiabudi Bandung - Nibras, Fatih; Vanya Azizah Hamida2; Prathya Tyara Sagarmatha3; Mohammad Akmal Zaky Putra Kusumah4; Teuku Muhammad Daffa Arullah5 (UNIVERSITAS INDO GLOBAL MANDIRI, 2024)
The many aisles with various types of goods in Borma Setiabudi make appropriate signage and wayfinding systems as well as visual identity very necessary so that visitors can find the goods they want easily. This is important for managing visitors, especially new visitors who are trying to find the items they are looking for when shopping. This research aims to analyze the visual identity contained in the signage that has been installed in Borma Setiabudi using a qualitative descriptive method, data was collected through direct observation in Borma complete with documentation of the signage. This research produces a comparison of existing signage in Borma Setiabudi with the criteria and regulations for making signage, apart from that, it also includes a comparison of relevant research results which also discuss visual identity and signage systems for other shopping centers in the Bandung area. This research resulted in the need for a plan to create a signage system that complies with regulations and standards in Borma because the existing signage does not meet the existing criteria. Adjustment and rework of signage is necessary to convey it more effectively to visitors. Keywords : Visual Identity, Signage System, Shopping Center